ANALISIS KUALITAS PELAYANAN, HARGA, FASILITAS DAN LOKASI TERHADAP KEPUASAN PELANGGAN (STUDI KASUS PADA PT. HAPPY KIDDY INDONESIA RANTAUPRAPAT) - Lumban Gaol, Slamat Andriani; Sumitro, Sumitro; Efendi Siregar, Zulkifli Musannif (Universitas Labuhanbatu, 2021)
This study aims to determine the Analysis of Service Quality, Price, Facilities and Location of Customer Satisfaction (Case Study at PT. Happy Kiddy Indonesia Rantauprapat). Data collection in this study was conducted through a survey approach with quantitative descriptive research type by distributing questionnaires to 30 respondents, while the population used in this study were visitors to Suzuya Mall at PT. Happy Kiddy Indonesia Rantauprapat. Data analysis tools used in this study used SPSS (Statistical Product Software Solution). The data analysis techniques in this study were descriptive analysis, multiple linear regression analysis, hypothesis testing using partial significance test (t test), simultaneous significant testing (F test). ), and testing the coefficient of determination (R2).